In Operando Neutron Scattering Multiple‐Scale Studies of Lithium‐Ion Batteries. Issue 19 (23rd February 2022) - Wang, Huibo; Ning, De; Wang, Litong; Li, Heng; Li, Qingyuan; Ge, Mingzheng; Zou, Junyan; Chen, Shi; Shao, Huaiyu; Lai, Yuekun; Zhang, Yanyan; Xing, Guichuan; et al.
Abstract: Real‐time observation of the electrochemical mechanistic behavior at various scales offers new insightful information to improve the performance of lithium‐ion batteries (LIBs). As complementary to the X‐ray‐based techniques and electron microscopy‐based methodologies, neutron scattering provides additional and unique advantages in materials research, owing to the different interactions with atomic nuclei. The non‐Z‐dependent elemental contrast, in addition to the high penetration ability and weak interaction with matters, makes neutron scattering an advanced probing tool for the in operando mechanistic studies of LIBs. The neutron‐based techniques, such as neutron powder diffraction, small‐angle neutron scattering, neutron reflectometry, and neutron imaging, have their distinct functionalities and characteristics regimes. These result in their scopes of application distributed in different battery components and covering the full spectrum of all aspects of LIBs. The review surveys the state‐of‐the‐art developments of real‐time investigation of the dynamic evolutions of electrochemically active compounds at various scales using neutron techniques. The atomic‐scale, the mesoscopic‐scale, and at the macroscopic‐scale within LIBs during electrochemical functioning provide insightful information to battery researchers. The authors envision that this review will popularize the applications of neutron‐based techniques in LIB studies and furnish important inspirations to battery researchers for the rational design of the new generation of LIBs. Abstract : The state‐of‐the‐art development of in operando and in situ neutron techniques is systematically summarized here to reveal the lithium dynamic processes in real‐time, such as the crystallographic changes, the surface evolution between the electrodes and electrolytes, and the lithium distribution transmission paths. The current challenges, applications, and future opportunities of in situ neutron technology in probing the lithium distribution for LIBs are also discussed.